Arte e interattività: per un’estetica dei sistemi - Macrì, Saverio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2023)
The article aims to show the influence exerted by Systems Theory and Cybernetics in the field of Aesthetics. By virtue of an approach that is pluralistic and open to different languages, both disciplines have offered artists and theorists useful tools of description and analysis to account for the phenomenon of interactivity. Systems theory provides suitable conceptual tools to define a new aesthetic object – the interactive installation – endowed with a participatory and relational nature, as well as a dynamic and continuously changing structure. Additionally, cybernetics provides artistic experiments featuring technological innovations with fundamental contributions on how computational systems can be employed to simulate performance akin to the behaviour of living organisms. The scope of such notions in aesthetics will be illustrated by analysing some works by the pioneers of interactive art: art critic Jack Burnham, artist and theorist Roy Ascott, and psychologist and cybernetician Gordon Pask.